Electrical Stimulation of the Anterior Thalamus for Epilepsy: Clinical Outcome and Analysis of Efficient Target. Issue 4 (8th October 2018) - Koeppen, Johannes Alexander; Nahravani, Fahimeh; Kramer, Martin; Voges, Berthold; House, Patrick Michael; Gulberti, Alessandro; Moll, Christian Karl Eberhard; Westphal, Manfred; Hamel, Wolfgang
Abstract : Objective: Deep brain stimulation (DBS) of the anterior thalamic complex (ANT) is an adjunctive therapy for pharmacoresistant epilepsy. To define the most efficient target in DBS for epilepsy, we investigate clinical data, position of leads, usability of atlas data compared to electric field modeling based on programming parameters. Methods: Data from ten consecutive patients who underwent ANT‐DBS were analyzed. The mammillothalamic tract (MTT), an internal landmark for direct stereotactic targeting, was segmented from MRI. Centers of stimulation were determined and their positions relative to ventricles and the MTT were analyzed. Two 3D thalamus atlases were transformed to segmented patient's thalami and proportions of activated nuclei were calculated. Results: Our data indicate higher response rates with a center of stimulation 5 mm lateral to the wall of the third ventricle ( R 2 for reduction of focal seizure frequency and distance to the wall of the third ventricle = 0.48, p = 0.026). For reduction of focal seizures, a strong positive correlation with the dorsal distance to the midcommissural plane was found ( R 2 = 0.66, p = 0.004). In one 3D atlas, stimulation of internal medullary lamina (IML) correlated strongly positive with response rates, which, however, did not reach statistical significance ( R 2 = 0.69, p = 0.17 for tonic–clonic seizures). All electrical fields covered the diameter of the MTT. The position of the MTT in the thalamus was highly variable (range: x ‐coordinate 4.0 to 7.3 mm, y ‐coordinate −1.3 to 5.1 mm in AC–PC space). Conclusions: The distance of the active contact to the lateral wall of the third ventricle, MTT and the ventrodorsal distance to midcommissural plane appear to be relevant for optimal target planning. For reduction of focal seizure frequency, we found best response rates with a center of stimulation 5 mm lateral to the wall of the third ventricle, and a lead tip 10 mm dorsal of the midcommissural plane.